![](http://h.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=44f1c94af01fbe091c0bcb125b50200b/1f178a82b9014a90c939b081ab773912b31bee83.jpg)
![](http://b.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=8be9131a0b24ab18e043e93105cacaf5/5d6034a85edf8db1129c8a580b23dd54564e7458.jpg)
①5√8-2√32+√50
=5*3√2-2*4√2+5√2
=√2(15-8+5)
=12√2
②√6-√3/2-√2/3
=√6-√6/2-√6/3
=√6/6
③(√45+√27)-(√4/3+√125)
=(3√5+3√3)-(2√3/3+5√5)
=-2√5+7√5/3
④(√4a-√50b)-2(√b/2+√9a)
=(2√a-5√2b)-2(√2b/2+3√a)
=-4√a-6√2b
⑤√4x*(√3x/2-√x/6)
=2√x(√6x/2-√6x/6)
=2√x*(√6x/3)
=2/3*|x|*√6
⑥(x√y-y√x)÷√xy
=x√y÷√xy-y√x÷√xy
=√x-√y
⑦(3√7+2√3)(2√3-3√7)
=(2√3)^2-(3√7)^2
=12-63
=-51
⑧(√32-3√3)(4√2+√27)
=(4√2-3√3)(4√2+3√3)
=(4√2)^2-(3√3)^2
=32-27
=5
⑨(3√6-√4)?
=(3√6)^2-2*3√6*√4+(√4)^2
=54-12√6+4
=58-12√6
⑩(1+√2-√3)(1-√2+√3)
=[1+(√2-√3)][1-(√2-√3)]
=1-(√2-√3)^2
=1-(2+3+2√6)
=-4-2√6
(1)5√12×√18
=5*2√3*3√2
=30√6;
(2)-6√45×(-4√48)
=6*3√5*4*4√3
=288√15;
(3)√(12a)×√(3a) /4
=√(36a^2)/4
=6a/4
=3a/2.
![](http://c.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=172639f6ad51f3dec3e7b162a4dedc27/500fd9f9d72a6059af1d10262a34349b033bbaf9.jpg)
![](http://e.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=4153f2dfd739b6004d9b07b1d9601912/9f2f070828381f30bdb97c95ab014c086e06f06e.jpg)
![](http://h.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=fe497c95ab014c08196e20a33a4b2e30/38dbb6fd5266d0161e496f14952bd40735fa35bd.jpg)